Digitization of the educational inspection of Andalusia - Sánchez Hermosilla, Manuel Jesús; Aguilar Rayo, Antonia; Pérez Aguilar, José Francisco; Pérez Galafate, Rosa María; Robles Chacón, Manuela María; Zulueta Castañeda, Manuel (Avances en Supervisión Educativa, 2020)
The different challenges of the information and knowledge society have been tried by the Educational Inspectorate of Andalusia to take advantage of the Seneca Information System and other institutional applications of messaging and exchange of information and documentation. These challenges, and especially the opportunities of the system outlined, give way to the digitization process of the Educational Inspectorate of Andalusia, which begins in the 2003-2004 academic year, progressively implementing the different modules for general functionalities, forging its own architecture in the Information System Seneca, and the scope of educational centers and services for access to information on these. The General Action Plan of the Educational Inspectorate of Andalusia, for the period 2019-2023, includes this legacy to, strategically, continue promoting the process of digitizing the work of the Educational Inspectorate, with the aim of streamlining and optimizing its planning , monitoring their processes and controlling the results of their actions. Once the above is developed, there would be more suitable conditions to implement the process-based management approach, in order to adequately respond to the new needs and realities of the recipients of the actions of the Educational Inspection, by having a support where to settle it in line with the digital society.